2005
DOI: 10.1002/ijc.21233
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive effect of 1,4-phenylene diisothiocyanate onN-butyl-N-(4-hydroxybutyl)nitrosamine-induced urinary bladder carcinogenesis in male ICR mice

Abstract: The modifying effects of dietary administration of 1,4-phenylene diisothiocyanate (DITC) on N-butyl-N-(4-hydroxybutyl) nitrosamine (BBN)-induced urinary bladder carcinogenesis during the initiation and post-initiation phases were examined in male ICR mice. Five-week-old animals were divided into 5 groups. Groups 1-3 were given BBN (500 ppm) in drinking water for 6 weeks starting at age 6 week. Mice in Group 2 were given the diet containing 100 ppm DITC for 8 weeks during the initiation phase, starting 1 week b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 57 publications
2
8
0
Order By: Relevance
“…[9][10][11][12] Genetic studies in mouse models have revealed a role for this receptor in the control of blood pressure 13 and renal fluid retention 14 15 in the kidney. PPARc was found to have tumour suppressor effects in the colon and other tissues [16][17][18][19][20][21] although controversy still exists regarding its role in the colon in mouse models of carcinogenesis. 22 In humans, an allelic variant of PPARc that exhibits increased sensitivity to ligand activation and is associated with a reduced risk of type II diabetes 23 appears to protect against colon adenomas.…”
mentioning
confidence: 99%
“…[9][10][11][12] Genetic studies in mouse models have revealed a role for this receptor in the control of blood pressure 13 and renal fluid retention 14 15 in the kidney. PPARc was found to have tumour suppressor effects in the colon and other tissues [16][17][18][19][20][21] although controversy still exists regarding its role in the colon in mouse models of carcinogenesis. 22 In humans, an allelic variant of PPARc that exhibits increased sensitivity to ligand activation and is associated with a reduced risk of type II diabetes 23 appears to protect against colon adenomas.…”
mentioning
confidence: 99%
“…We previously reported that ceratin cancer chemopreventive agents reduced the incidence and multiplicity of epithelial malignancy in the target tissues by lowering the cyclin D1-positive ratio (16,25,26,28,29,38,39). A significant relationship between cyclin D1 over-expression and tumor grade or stage was also reported in human transitional cell carcinomas (32).…”
Section: ------------------------------------------------------------mentioning
confidence: 92%
“…In the current study, ß-cryptoxanthin effectively suppressed cyclin D1-positive cell ratios of various urinary bladder lesions, implying that reduction in the incidence of tumors and preneoplastic lesions of urinary bladder is related to effectively suppressed cell cycle progression by the treatment with ß-cryptoxanthin. In a previous study, selective cyclin D1 inhibitors, silymarin (25) and 1,4-phenylene diisothiocyanate (26), possessed chemopreventive potential on BBN-induced urinary bladder carcinogenesis in male ICR mice.…”
Section: ------------------------------------------------------------mentioning
confidence: 98%
See 1 more Smart Citation
“…They include astaxanthin [224], protocatechuic acid [225], diosmin [226], hesperidin [226], silymarin [227], 1,4-phenylene diisothiocyanate [228], and β -cryptoxanthin [229]. These compounds are ready to be evaluated for efficacy in clinical trials.…”
Section: Prevention Of Bladder Cancermentioning
confidence: 99%